2008
DOI: 10.1016/j.jtcvs.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of risk algorithms in predicting early and late operative outcomes in high-risk patients undergoing aortic valve replacement

Abstract: The STS Predicted Risk of Mortality most accurately predicted perioperative and long-term mortality for the highest risk patients having aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 355 publications
(181 citation statements)
references
References 14 publications
8
156
1
16
Order By: Relevance
“…The surgical outcomes in this trial were excellent, as compared with those in studies involving high-risk patients with aortic stenosis. [16][17][18][19][20][21] In the as-treated population, the ratio of observed operative mortality to predicted mortality (according to the risk model of the Society of Thoracic Surgeons) was 0.68. Rates of death in the transcatheter group at 30 days (3.4% in the intention-to-treat analysis and 5.2% in the as-treated analysis) were also excellent, as compared with earlier results in the PARTNER trial in patients who were not candidates for surgical valve replacement 35 and with data from other registries of transcatheter replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical outcomes in this trial were excellent, as compared with those in studies involving high-risk patients with aortic stenosis. [16][17][18][19][20][21] In the as-treated population, the ratio of observed operative mortality to predicted mortality (according to the risk model of the Society of Thoracic Surgeons) was 0.68. Rates of death in the transcatheter group at 30 days (3.4% in the intention-to-treat analysis and 5.2% in the as-treated analysis) were also excellent, as compared with earlier results in the PARTNER trial in patients who were not candidates for surgical valve replacement 35 and with data from other registries of transcatheter replacement.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Although surgical aortic-valve replacement improves symptoms and survival, [11][12][13][14][15] observational studies have identified various subgroups of patients (i.e., those with an advanced age and those with poor left ventricular function or other coexisting disorders) who are at increased risk for operative complications or death. [16][17][18][19][20][21] In such patients, a less invasive treatment may be a desirable alternative.…”
mentioning
confidence: 99%
“…TAVI has demonstrated the potential to decrease the morbidity associated with standard SAVR owing to the avoidance of a median sternotomy, cardiopulmonary bypass and cardioplegic arrest. Nevertheless, the selection process towards TAVI needs thoughtful consideration of risks and benefits of the procedure and a comparison of these factors with alternative therapies [13] . The EACTS/ESC Guidelines recommend four main steps for patient selection before TAVI procedure: severity of valve stenosis and symptom confirmation, assessment of the technical feasibility, exclusion of contraindications, and accurate clinical examination for surgical risk assessment based on validated scores [14] .…”
Section: High-risk Patientsmentioning
confidence: 99%
“…The STS-PROM score appears to be more reliable than the EuroSCORE for predicting outcomes of high-risk AVR patients. However, STS-PROM tends to underestimate mortality (Dewey et al, 2007). A meta-analysis showed EuroSCORE to have low discrimination ability for valve surgery and it slightly over predicted risk (Parolari et al, 2010), particularly for octogenarians referred for AVR (Leontyev et al, 2009).…”
Section: Risk Assessment and Patient Selectionmentioning
confidence: 99%